The secret life of CFTR as a calcium‐activated chloride channel. (30th September 2013) - Billet, Arnaud; Hanrahan, John W.
Abstract : Abstract  cAMP‐stimulated anion conductance is defective in cystic fibrosis (CF). The regulatory domain of CFTR, the anion channel protein encoded by the CF gene, possesses an unusually high density of consensus sequences for phosphorylation by protein kinase A (14 in a stretch of <200 amino acids). Thus it is not surprising that CFTR is viewed primarily as a cAMP‐stimulated anion channel, and most studies have focused on this mode of activation. However, there is growing evidence that CFTR also responds to Ca 2+ ‐mobilizing secretagogues and contributes substantially to cholinergic and purinergic responses in native tissues. G protein‐coupled receptors that signal through Gαq can stimulate CFTR channels by activating Ca 2+ ‐dependent adenylyl cyclase and tyrosine kinases, and also by inhibiting protein phosphatase type 2A. Here we review evidence for these novel mechanisms of CFTR activation and discuss how they may help explain previous observations.